Knowledge, Self Efficacy and Stress in Patient with Leprosy through Implementation of Support Group using Adaptation Theory - Margareta Kewa Lamak; Kusnanto Kusnanto; yulis Setiya Dewi (Jurnal Ners, 2014)
Introduction: Assumption of leprosy that it is uncurable, hereditary, cursed, and impure disease causes the patients angry, disappointed even being introvert and leads them to a treatment adherence. The goal of this study was to explain the increasing of knowledge, self efficacy and the decreasing of stress in patient with leprosy by support group in Leprosy Hospital of Sumberglagah.Methods: This study was a quasy experiment study using pre test and post test nonequivalent control. Total sample was 28 respondents in inpatient ward and outpatient. The instruments were questionnaire and cortisol level. Data were then analyzed descriptively and statistically using Wilcoxon test, Mann-whitney test, paired test and independent t test with α 0,05.Results: Results showed that mean of age was 40,92 years old. Almost all of respondents were in primary education. Knowledge pre and post was 57,14% good; 100% good (p = 0,041). Self effi cacy pre and post was 42,86% high; 28,57% high (p = 0,307). Stres level pre and post was 35,71% normal; 50% normal (p = 0,046). Mean of cortisol level pre and post was 66,35 ± 28,72; 71,80 ± 23,84 (p = 0,598).Discussion: It can be concluded that support group increases knowledge and decreases stress but doesn’t increase self effi cacy and decrease cortisol level in patient with leprosy in Leprosy Hospital of Sumberglagah.